Marketing 5.0 : the role of human-mimicking technology - Kumar, Ajay; Ciddikie, M. D.; Kashyap, Anil Kumar; Akram, Hafiz Wasim (Emerald Publishing Limited, 2025)
Marketing 5.0: The Role of Human-Mimicking Technology focuses on 'human-mimicking technology' in the age of marketing, wherein consumers and technology are blended as one. It reimagines technology creating a human touch, which not only enhances the customer experience but also builds an ecosystem of personalised sense-and-respond experiences, leading towards greater sustainability. It is this age of Augmented and Agile marketing, which delivers tech-empowered human interaction at pace and scale, achieving the perils and promises of digitalization. Marketing is witnessing a shift from Marketing 4.0 to Marketing 5.0. In this change, there is a continuous struggle for gaining digital business presence. Marketing 5.0 introduces academics and marketers to the concept of human-mimicking technologies to create, communicate, deliver, and enhance value across the customer journey. The objective is to learn and understand the blended approach, where consumers and technology integrate as one. Marketing 5.0 explores the importance of technology to marketing 5.0 and will be of benefit to practitioners, academics, and industry researchers, and students at master's and doctoral levels.